KOSMAS-GYTHIO UNIT: A METAMORPHIC CARBONATE SEQUENCE OVERLYING THE PHYLLITES-QUARTZITES UNIT IN SOUTHERN PELOPONNESUS, GREECE. - Skourtsos, E.; Lekkas, S. (Bulletin of the Geological Society of Greece, 2004)
New data from southern Peloponnesus show the presence of a metamorphic carbonate sequence sandwiched between the Phyllites Quartzites and the Tyros beds, the permothassic base of the Tripolitza unit. The lithostratigraphic members of this sequence, named Kosmas Gythio unit, are comparable to that of the Plattenkalk unit in Taygetos and Parnon mountains. It is suggested that palaeogeographically the unit belongs to the Ionian basin and its position was between the Plattenkalk unit and the Tripolitza carbonate platform. As for the Phyllites-Quartzites unit it is suggested that this unit is not a metamorphic equivalent to the Tyros Beds or the basement of the Tripolitza platform, but the base or the basement of the Kosmas-Gythio unit, and therefore of the Ionian basin.